Hepatic resection after transarterial chemoembolization increases overall survival in large/multifocal hepatocellular carcinoma: a retrospective cohort study - Chen, Junwei (Oncotarget, 2016)
To investigate the prognosis of transarterial chemoembolization (TACE) followed by hepatic resection (HR) in large/multifocal hepatocellular carcinoma (HCC), the medical records of consecutive HCC patients who underwent TACE between January 2006 and December 2010 were retrospectively analyzed. Patients who received TACE alone comprised the T group (61 patients), while those who received HR after TACE comprised the T+R group (49 patients). All the resections were successfully performed, and only one class V complication occurred. While liver function was altered from baseline within 1 week after HR, it recovered within 1 month. Overall survival (OS) of the T+R and T groups were compared, and sub-group analyses were performed based on baseline α-fetoprotein (AFP) levels, the reduction of AFP, and tumor response before HR. Overall survival (OS) in the T+R group was longer than in the T group (47.00 ± 2.87 vs. 20.00 ± 1.85 months, P < 0.001). OS in the T+R group with AFP reduction was less than 50%, and OS among those with a poor tumor response before HR did not differ from the T group (P > 0.05). These patients may not benefit from the combined treatment. Our findings suggest HR after TACE is safe and effective for large/multifocal HCC, and prolongs OS when compared to TACE alone.